Answer:
Option (D) is correct.
Step-by-step explanation:
In a triangle BCD , with b, c, d as the sides of triangle.
Sine rule states when we we divide side b by the sine of angle B then it is equal to side c divided by the sine of angle C and also equal to side d divided by the sine of angle D.
Using Sine rule,
![\frac{b}{\sin B}=\frac{c}{\sin C}=\frac{d}{\sin D}](https://tex.z-dn.net/?f=%5Cfrac%7Bb%7D%7B%5Csin%20B%7D%3D%5Cfrac%7Bc%7D%7B%5Csin%20C%7D%3D%5Cfrac%7Bd%7D%7B%5Csin%20D%7D)
Consider the first and third ratio,
![\frac{b}{\sin B}=\frac{d}{\sin D}](https://tex.z-dn.net/?f=%5Cfrac%7Bb%7D%7B%5Csin%20B%7D%3D%5Cfrac%7Bd%7D%7B%5Csin%20D%7D)
Substitute the values of d = 3 , b= 5 and ∠D=25°
![\Rightarrow \frac{5}{\sin B}=\frac{3}{\sin 25^{\circ}}](https://tex.z-dn.net/?f=%5CRightarrow%20%5Cfrac%7B5%7D%7B%5Csin%20B%7D%3D%5Cfrac%7B3%7D%7B%5Csin%2025%5E%7B%5Ccirc%7D%7D)
Thus, Measure of angle B is 45 and 135 as sinB is positive is first and 2nd quadrant.
Thus, option (D) is correct.
Since you subtract 16 from the y value, P is (-2, 6), and the y value comes second (meaning that it's 6), we get 6-16=-10
Answer:
The statement is true that a function is a relation in which each y value has ONLY 1 x value.
Step-by-step explanation:
The statement is true that a function is a relation in which each y value has ONLY 1 x value.
The reason is very clear that we can not have the repeated x-values (two same x-values).
For example, given the set of the ordered pairs of a relation
{(3, a), (6, b), (6, c)}
As the same x values (x=6) has two different Y values. Hence, the stated relation is not a function.
In order to be a function, a relation must have only 1 x-value for each y-value.
Therefore, the statement is true that a function is a relation in which each y value has ONLY 1 x value.
<span>
y = 7 + 3/5
y = 35/5 + 3/5
y = 38/5
y = 2*(38/5)
y = 76/10
---
lunch time:
z = 1/2
z = 5*(1/2)
z = 5/10
---
time switching classes:
w = 7/10
---
y - 6x - z - w = 0
6x = y - z - w
x = (y - z - w)/6
x = (76/10 - 5/10 - 7/10)/6
x = (76 - 5 - 7)/(10*6)
x = (64)/(10*6)
x = (2*2*2*2*2*2)/(2*5*2*3)
x = (2*2*2*2)/(5*3)
x = 16/15
x = 1.0666666666
---
check:
y = 7 + 3/5
y = 7.6
z = 1/2
z = 0.5
w = 7/10
w = 0.7
y - 6x - z - w = 0
6x = y - z - w
x = (y - z - w)/6
x = (7.6 - 0.5 - 0.7)/6
x = 1.0666666666
answer:
1.07 hours</span>